Concentration Test of Binahong (Anredera cordifolia) Leaf Extracts on Growth, Years and Severity Leaf Blight Disease of Red Onion(Allium ascalonicum L.) Plant - Zahanis Zahanis; Milda Ernita; Rahmat Hidayat; Devi Purnamasari; Salsabila Tri Rahmi (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2023)
This study presents an investigation into the optimal concentration of binahong (Anredera cordifolia) extract for enhancing the growth, yield, and mitigating leaf blight in shallots. Conducted within a controlled environment at a well-established laboratory, the experiment employed a completely randomized design (CRD) to evaluate the effects of five different concentrations of binahong leaf extract. Data analysis included variance tests, and when significant effects were identified, Duncan's multiple range test (DMRT) was employed to further examine the results. The findings demonstrate that a 30% concentration of binahong (Anredera cordifolia) extract significantly improves growth, yield, and effectively suppresses the development of Red onion(Allium ascalonicum L.) leaf blight. Moreover, this concentration resulted in a wet tuber weight per hill of 76.30 g. These insights contribute to the development of sustainable agricultural practices and offer a promising alternative to chemical-based treatments for managing crop diseases, thereby advancing our understanding of the potential applications of binahong (Anredera cordifolia) extract in agricultural settings.